Rice β-glucosidase Os12BGlu38 is required for synthesis of intine cell wall and pollen fertility. (27th September 2021) - Shim, Su-Hyeon; Mahong, Bancha; Lee, Sang-Kyu; Kongdin, Manatchanok; Lee, Chanhui; Kim, Yu-Jin; Qu, Guorun; Zhang, Dabing; Ketudat Cairns, James R; Jeon, Jong-Seong
Abstract : Characterization of a rice glycoside hydrolase family1 mutant, os12bglu38, reveals that a plasma membrane-associated β-glucosidase is necessary for proper intine development. Abstract: Glycoside hydrolase family1 β-glucosidases play a variety of roles in plants, but their in planta functions are largely unknown in rice ( Oryza sativa ). In this study, the biological function of Os12BGlu38, a rice β-glucosidase, expressed in bicellular to mature pollen, was examined. Genotype analysis of progeny of the self-fertilized heterozygous Os12BGlu38 T - DNA mutant, os12bglu38-1, found no homozygotes and a 1:1 ratio of wild type to heterozygotes. Reciprocal cross analysis demonstrated that Os12BGlu38 deficiency cannot be inherited through the male gamete. In cytological analysis, the mature mutant pollen appeared shrunken and empty. Histochemical staining and TEM showed that mutant pollen lacked intine cell wall, which was rescued by introduction of wild-type Os12BGlu38 genomic DNA. Metabolite profiling analysis revealed that cutin monomers and waxes, the components of the pollen exine layer, were increased in anthers carrying pollen of os12bglu38-1 compared with wild type and complemented lines. Os12BGlu38 fused with green fluorescent protein was localized to the plasma membrane in rice and tobacco. Recombinant Os12BGlu38 exhibited β-glucosidase activity on the universal substrate p -nitrophenyl β-d -glucoside and some oligosaccharides and glycosides. These findings provide evidence that function of a plasma membrane-associated β-glucosidase is necessary for proper intine development.